'Good mums don't, apparently, wear make-up': negotiating discourses of gendered parenthood in Mumsnet Talk. (29th December 2016) - Mackenzie, Jai
Abstract : This article explores the discourses and related subject positions that are negotiated by contributors to the discussion forum of a popular British parenting website, Mumsnet Talk. Drawing on analysis of a single thread posted to this forum, I explore the ways in which participants, who present themselves as women and as parents, negotiate dominant discourses of gendered parenthood that position them as 'mothers', and often, by association, as the primary caregiver, who is defined and positioned exclusively in relation to children. I also show that contributors use a range of linguistic and digital resources to challenge such discourses, and that their resistance can be facilitated, at times, by the affordances of the forum itself. The potential to connect with a large community of Mumsnet users, for example, is identified as a powerful resource at their disposal. Overall, I find that Mumsnet Talk is a fruitful site for negotiating, resisting and subverting socio-cultural norms and expectations, but that it remains difficult here, as elsewhere, for women to escape dominant discourses that work to position them in restrictive gendered subject positions.